One Class of Predicates Reflecting Conceptualization of Time as a Resource - E. R. Ioanesyan (Научный диалог, 2021)
The research presented in the article was carried out within the framework of the conceptual and metaphorical theory of J. Lakoff and M. Johnson. One of the conceptual metaphors related to the conceptual metaphors of European culture is the metaphor TIME IS A LIMITED RE-SOURCE, TIME IS A VALUE. The meaning ‘to waste time’ is noted in the Russian verb to lose, French perdre, gaspiller, Spanish perder, Italian perdere, English lose, waste, misspend, squander, German verlieren, etc. Using the example of the Russian verb to lose, the classes of use of these predicates in the indicated meaning are presented in the article, as well as some features of the French and English units reflecting the specific features of the worldview of these languages are not-ed. The research is based on a large corpus of explanatory and bilingual dictionaries, data from linguistic corpuses. The relevance of the study is determined by the fact that, as it has been noted by the authors of the conceptual theory of metaphor, the basic values of culture are consistent with the metaphorical structures of its basic concepts. The relevance of the study is also determined by the fact that the study of metaphorical concepts is one of the ways to reconstruct the linguistic picture of the world.